Temporal sequence of greyscale ultrasound changes and their relationship with neovascularity and pain in the patellar tendon. Issue 13 (12th January 2009) - Malliaras, P; Purdam, C; Maffulli, N; Cook, J
Abstract : Objective: Ultrasound (US) imaging has revealed distinct types of greyscale abnormalities in the patellar and Achilles tendons, including diffusely thickened tendons and tendons containing a hypoechoic region. The relationship between these greyscale abnormalities and their clinical relevance is unknown. This study investigated the temporal sequence in greyscale abnormalities as well as the relationship between greyscale abnormalities, Doppler flow and pain. Methods: Patellar tendon pain (single leg decline squat test) and ultrasound imaging (greyscale (normal, diffuse thickening, hypoechoic), presence of Doppler flow) were assessed bilaterally among 58 volleyball players at monthly intervals during a 5-month season. The probability of transition between the greyscale ultrasound groups was calculated for each month and totalled over the season (prospective) and the relationship between these groups and the presence and intensity of pain and the presence of Doppler flow were investigated (cross-sectional investigation). Results: Tendons with normal US were more likely to transition to diffuse thickening than to a hypoechoic region. Tendons containing a hypoechoic region were more likely to transition to diffuse thickening rather than to a normal US appearance. Hypoechoic regions were more likely to be painful (59%) and contain Doppler flow (42%) than tendons with diffuse thickening (pain in 43% and Doppler flow in 6%). Conclusions: The transitions identified between normal, diffusely thickened tendons and those containing a hypoechoic region suggests that these greyscale US changes may represent different phases of tendon pathology. Tendons containing a hypoechoic region are more likely to be painful and contain Doppler flow than diffusely thickened tendons.